Pengaruh Model Latihan dan Indeks Massa Tubuh Terhadap Stamina Atlet Golden Karate Squad Banjarnegara - prakoso, dodik (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research analyzes the influence of the Stage Circuit Training and Oregon Circuit Training training models on normal body mass index status and mild obesity body mass index as well as the interaction between the training models and (Stage Circuit Training and Oregon Circuit Training) and body mass index on increasing the stamina of Golden Athletes. Karate Squad Banjarnegara. Experimental research method with a two-factor design (2x2), data analysis using Analysis of Variant (Anova) 2x2 factorial design at the significance level (α: 0.05), and hypothesis testing using the General Linear Model (GLM) Two Way Anova. The population of this study was 16 athletes. The results of the research show that there is a difference between the Stage Circuit Training and Oregon Circuit Training training methods on increasing VO2Max (Fcount 10.199 and sig 0.000), and the difference between the Stage Circuit Training and Oregon Circuit Training training methods on the fatigue index (Fcount 47.391 and sig 0.000). There is a significant difference between normal body mass index and mild obesity body mass index on increasing VO2Max (Fcount 43.825 and sig. 0.000), and there is a difference between normal body mass index status and mild obesity body mass index on fatigue index (Fcount 9.355 and sig 0.010). The interaction of training methods (Stage Circuit Training and Oregon Circuit Training) and body mass index on VO2Max and fatigue index obtained sig values ​​of 0.022 and 0.041. The conclusion is that there are differences in the influence of the Stage Circuit Training and Oregon Circuit Training models, as well as normal body mass index status and mild obesity body mass index status on increasing athlete stamina. There is also an interaction between training models (Stage Circuit Training and Oregon Circuit Training) and body mass index in improving the stamina of Golden Karate Squad Banjarnegara karate athletes. Keywords: Training Model, Body Mass Index, Athlete Stamina